Perbedaan Komunikasi Kerja Dari Karyawan PNS dan Swasta - joko Pramono (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2018)
The communication research on employee performance has been widely carried out, but the results of the study have not shown consistency. This study examines whether employee status (The Government Employee- PNS or Private) interacts with the communication variabels in influencing employee performance. Employee status which is a proxy of different organizational structures is designed as a dummy variable. The study was conducted on working students at Bekasi Unisma. The results showed that the communication variabel (X1) and employee status (X2) had an effect on employee performance, but the interaction of X1 and X2 were not significant. Based on the results of this study, we are suggested that organizations have to manage their communication activities well